TINGKAT PRODUKSI SUSU DAN KESEHATAN SAPI PERAH DENGAN PEMBERIAN ALOE BARBADENSIS MILLER - Siti Aisyah (Jurnal Gamma, 2011)
Siti AisyahStaf Pengajar Jurusan Teknologi Industri Petyernakan, Fakultas Pertanian-Peternakan ,Universitas Muhammadiyah MalangAlamat Korespondensi : Jl.Mt Hariono V/205 MalangTelpon : 0341 551285, Hp : 08883863160.ABSTRACTBAloe vera plants on liliciae group that has 150 nutrition pregnancies, shaped mineral, proteinshaped sour merging amino esensial with enzymes, fat shaped steroid also found saponin work asantiseptik, analgesik, counter germ, counter virus, counter mushroom and worm this watchfulnessaims to detect potential Aloe barbadensis miller towards milk quality that is fat degree, protein, withbj and milk quantity with dairy cattle well-being. experimen this carried out in dairy cattle husbandryat area KUD Pujon.Aloe vera this applied in 15 dairy cattle beginning laktasi/laktasi I with different concentrationthat is 0 kg, 1 kg, 2 kg, 3 kg and 4 kg; each repeated 3 times. then canvassed degree protein, fat, BJ,total milk production with healthy status dairy cattle.The research result shows that not found a marked difference in degree protein, fat degree,with bj and milk production total delivers treatment without aloe vera with aloe vera. although suchstill got value exceeds value kodex operative at Indonnesia.Cow well-being status is got enough good because painfulness number 0 and endoparasit aftergift aloe vera got, not influential after gift 6 days and after gift 12 days endoparasitexisting onlyinfestasi degree light and a large part infestasi degree 0 (zero/negative).Conclusion from this watchfulness aloe vera good enough is used for supplement addition fordairy cattle but must dryer to more nutrition degree;. this gift effect can appear after 12 gift daysAloe barbadensis miller.keyword: aloe vera, degree protein, fat degree, BJ dan well-being status.